Problems of administrative and legal regulation of disciplinary responsibility of the personnel of the criminal and executive service of Ukraine - Korostashivets, Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The urgency of studying the problems of administrative and legal regulation of disciplinary responsibility of the personnel of the State Criminal and Executive Service of Ukraine is due to a number of objective reasons: firstly, basic institutions of law enforcement officers’ disciplinary responsibility that were formed in the Soviet period have not changed significantly in modern conditions; secondly, in connection with the formation of a unified anti-corruption policy for the entire system of the civil service at the state level, new types of disciplinary misconduct of staff have been acquired; thirdly, the by-laws in the field of disciplinary responsibility of the penitentiary system staff are imperfect and do not fully "fill" the legislative gaps. The purpose of the article is to identify the main problems of administrative and legal regulation of disciplinary responsibility of the personnel of the State Criminal and Executive Service of Ukraine and develop proposals for their solution. It is stated that in the absence of a legislative definition of disciplinary misconduct of the State Criminal and Executive Service of Ukraine it is impossible to clearly distinguish it from other types of offenses, and this leads to the fact that the qualification of such an act as a disciplinary offense is at the discretion of the head. There are no rules specifying the stages of disciplinary proceedings, rules that contain a list of circumstances that preclude the involvement of staff in disciplinary action, circumstances that mitigate and aggravate disciplinary responsibility. The necessity of legislative regulation of the issue of official discipline of junior enlisted and command staff of the SCES of Ukraine is substantiated, and therefore at the time of adoption of the Law of Ukraine "On Disciplinary Statute of the Penitentiary System" and the Law of Ukraine "On the Penitentiary System", which will determine the procedure. Improving the legislation on administrative and disciplinary responsibility of junior enlisted and command staff requires a clear systematization of administrative and disciplinary legislation, in particular, through its codification, which should cover the rules of both substantive and procedural law.